2008
DOI: 10.1534/genetics.107.070813
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Genetically Defined Allele Classes in the Caenorhabditis elegans DAF-2 Insulin/IGF-1 Receptor

Abstract: The DAF-2 insulin/IGF-1 receptor regulates development, metabolism, and aging in the nematode Caenorhabditis elegans. However, complex differences among daf-2 alleles complicate analysis of this gene. We have employed epistasis analysis, transcript profile analysis, mutant sequence analysis, and homology modeling of mutant receptors to understand this complexity. We define an allelic series of nonconditional daf-2 mutants, including nonsense and deletion alleles, and a putative null allele, m65. The most sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 84 publications
2
99
0
Order By: Relevance
“…Because this contradicted the weak anti-apoptotic role previously reported for daf-2 in the worm germline, 12,13 we examined two additional alleles of daf-2 ( Figure 1b) and ablated daf-2 by RNA interference (RNAi) (see below). Even though the e1370, e1391 and m596 alleles affect distinct regions of the daf-2 locus, 14 all three mutations caused strong resistance to apoptosis. We also quantified IR-induced apoptosis in daf-2(e1370) mutants grown at 201C, where only 15% of larva form dauers, and found that resistance to DNA damage was preserved (see Figure 4b) but not at the permissive temperature of 151C (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Because this contradicted the weak anti-apoptotic role previously reported for daf-2 in the worm germline, 12,13 we examined two additional alleles of daf-2 ( Figure 1b) and ablated daf-2 by RNA interference (RNAi) (see below). Even though the e1370, e1391 and m596 alleles affect distinct regions of the daf-2 locus, 14 all three mutations caused strong resistance to apoptosis. We also quantified IR-induced apoptosis in daf-2(e1370) mutants grown at 201C, where only 15% of larva form dauers, and found that resistance to DNA damage was preserved (see Figure 4b) but not at the permissive temperature of 151C (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…terminal arrest phenotype. Consistent with this interpretation, the null phenotype of daf-2 includes embryonic lethality (Gems et al 1998;Patel et al 2008). However, daf-2 mutants are temperature sensitive, and Baugh and Sternberg (2006) showed that constitutive L1 arrest of daf-2 (e979) could be reversed at the permissive temperature producing reproductive adults.…”
Section: Daf-2/insrmentioning
confidence: 87%
“…The daf-2(e1368) allele has a mutation in the extracellular domain of the protein and is weaker than the e1370 allele, which has an intracellular mutation (Patel et al 2008). A total of 250 mm glucose stress suppressed dauer formation in both the daf-2 insulin-like receptor alleles ( Figure 6B).…”
Section: ; Mondoux Et Al 2010)mentioning
confidence: 99%